2013
DOI: 10.4172/2168-9296.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of Developmental and Reproductive Toxicity of Ortho- Phenylphenol (OPP) and Sodium Ortho-Phenylphenate (SOPP)

Abstract: Background: Due to widespread usage, the general public including pregnant women is routinely exposed to the fungicides, Ortho-Phenylphenol (OPP) and Sodium Ortho-Phenylphenate (SOPP), from many sources. Previous data reviews concluded no effects on development or reproduction in animal studies but upon re-analysis we realize that alternative interpretation may exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sodium orthonitrophenolate (OPP) also used as fungicides after harvest treatment of citrus fruits and as disinfectants and preservatives [FAO]. Moreover widely used in agricultural and disinfectants in food utensil [5] reported that rats and mice treated with multi dose of OPP (0,25.10,25) reveal diminish fetal body weight, high incidences in delayed skeletal ossification and Percent postimplantation loss (12.2; 16.7; 19.2; 18.3) respectively. In addition, fetal mice treated with SOPP showed malformation (mice: cleft plate; rabbits: resorptions).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium orthonitrophenolate (OPP) also used as fungicides after harvest treatment of citrus fruits and as disinfectants and preservatives [FAO]. Moreover widely used in agricultural and disinfectants in food utensil [5] reported that rats and mice treated with multi dose of OPP (0,25.10,25) reveal diminish fetal body weight, high incidences in delayed skeletal ossification and Percent postimplantation loss (12.2; 16.7; 19.2; 18.3) respectively. In addition, fetal mice treated with SOPP showed malformation (mice: cleft plate; rabbits: resorptions).…”
Section: Introductionmentioning
confidence: 99%